To have and to hold: touch and the vinyl resurgence - Harper, A (Cambridge University Press, 2018)
This article reviews a recent wave of literature on the resurgence of vinyl records, examining what it has claimed about vinyl's capacity for tangibility and the contrast to digital media, associated with intangibility. These claims are explained with reference to other literatures on touch, and it is suggested that vinyl's haptics mediates and embodies the emotionally rewarding production of a sense of self. The apparent contrast of vinyl aesthetics with classical music aesthetics is also discussed, and the presence of contemporary classical music within the vinyl resurgence is considered.